Pengaruh Pelayanan terhadap Kepuasan Anggota pada Koperasi Pegawai Perkebunan (KOP-BUN) Provinsi Sumatera Barat - Reni Respita; Detman, Detman; Musri, Musri (Indo-MathEdu Intellectuals Journal, 2025)
Service quality serves as a key factor determining satisfaction and loyalty; therefore, improving service standards is a crucial step toward cooperative sustainability. This study aims to examine the effect of service quality on member satisfaction at the Plantation Employees Cooperative (KOP-BUN) of West Sumatra Province. As a people-based economic institution, cooperatives play an essential role in enhancing the welfare of their members. A descriptive quantitative approach was applied with a population of 78 cooperative members selected using the total sampling technique. Data were collected through a five-point Likert scale questionnaire. The analysis employed simple linear regression and t-test to determine the effect of service quality on member satisfaction. The findings reveal that service quality has a positive and significant impact on member satisfaction. The regression coefficient of 0.096, with t-count (2.414) greater than t-table (1.992) and a significance level of 0.018 < 0.05, indicates that higher service quality leads to greater member satisfaction. The study implies that cooperatives need to enhance responsiveness, clarity of information, and staff empathy to maintain and improve member satisfaction levels.